Caring for our common home : a practical guide to Laudato Si' - Wright, Catherine (Assistant Professor of Religion and Philosophy) (Paulist Press, 2020)
"Living Laudato Sí connects the problems facing our common home with both the theology of Laudato Si' and concrete, hope-filled activities Christians are undertaking to mitigate our ecological crises and inspire the deep commitment to creation the gospel demands"--